Sensitive persuasion in syncretic text: a reading sociossemiótica - Torres, Lyssandra Maria Costa (2017)
Discursive Semiotics, of French origin, studies the argument as a set of discursive strategies used in persuasion. According to this theoretical approach, the efficiency of the argument depends on agreements between value systems, a declarative contract based on a shared belief between enunciator and enunciatee. Thus, the argument refers to the mechanisms deployed by the enunciator to the enunciatee believe enunciated speech to consequently achieve their adherence to a particular make. To analyze the strategies of persuasion / argument in the syncretic texts, we need to consider a global enunciation that articulates the different languages to produce grounded sense of effects not only in the intelligible dimension of discourse, but also in its sensitive dimension. Based on regimes of sense, proposed by Eric Landowski (2014), this article looks at an advertisement of a cosmetic magazine to show how different regimes of sense, including, programming, handling and adjustment, determine different strategies sensitive persuasion in syncretic text. At the end, you want to demonstrate that the effectiveness of sensitive persuasion lies in choosing strategies that take the enunciatee not only to adhere to a way of thinking, but also a way of feeling.